The Role of the PERK/eIF2α/ATF4/CHOP Signaling Pathway in Tumor Progression During Endoplasmic Reticulum Stress - Rozpedek, W.; Pytel, D.; Mucha, B.; Leszczynska, H.; Diehl, J.A.; Majsterek, I. (Current Molecular Medicine, 2016)
Hypoxia is a major hallmark of the tumor microenvironment that is strictly associated with rapid cancer progression and induction of metastasis. Hypoxia inhibits disulfide bond formation and impairs protein folding in the Endoplasmic Reticulum (ER). The stress in the ER induces the activation of Unfolded Protein Response (UPR) pathways via the induction of protein kinase RNA-like endoplasmic reticulum kinase (PERK). As a result, the level of phosphorylated Eukaryotic Initiation Factor 2 alpha (eIF2α) is markedly elevated, resulting in the promotion of a pro-adaptive signaling pathway by the inhibition of global protein synthesis and selective translation of Activating Transcription Factor 4 (ATF4). On the contrary, during conditions of prolonged ER stress, pro-adaptive responses fail and apoptotic cell death ensues. Interestingly, similar to the activity of the mitochondria, the ER may also directly activate the apoptotic pathway through ER stress-mediated leakage of calcium into the cytoplasm that leads to the activation of death effectors. Apoptotic cell death also ensues by ATF4-CHOP- mediated induction of several pro-apoptotic genes and suppression of the synthesis of anti-apoptotic Bcl-2 proteins. Advancing molecular insight into the transition of tumor cells from adaptation to apoptosis under hypoxia-induced ER stress may provide answers on how to overcome the limitations of current anti-tumor therapies. Targeting components of the UPR pathways may provide more effective elimination of tumor cells and as a result, contribute to the development of more promising anti-tumor therapeutic agents.
Keywords: apoptosis